Trichomonas vaginalis and Associated Factors among Pregnant Women Attending Antenatal Care at Bule Hora University Teaching Hospital, Oromia Region, Southern Ethiopia - Oliyad Husen; Alqeer Aliyo; Kalicha Boru; Tibeso Gemechu; Wako Dedecha; Girma Ashenafi (Journal of Parasitology Research)
Trichomoniasis is caused by a flagellated protozoan parasite called Trichomonas vaginalis. It is one of the most common, curable nonsexually transmitted infections globally. In Ethiopia, complications associated with genital infection in pregnant women are a common problem. Despite the burden of the disease, epidemiological data related to this disease is currently rare in Africa, particularly in Ethiopia. Objective. This research is aimed at assessing the prevalence of Trichomonas vaginalis and associated factors among pregnant women attending antenatal care at Bule Hora University Teaching Hospital. Methods. An institutional-based cross-sectional study was conducted among 196 pregnant women attending ANC at Bule Hora University Teaching Hospital. Structured questionnaires were used to collect sociodemographic and associated factor data. The consecutive sampling technique was used to include study participants. The two vaginal swabs were collected by brushing the vagina with a sterile cotton swab and tested by using direct wet mount and the Giemsa staining. The data were analyzed using SPSS version 26 for logistic regression analysis. A p value < 0.05 with 95% CI was used to declare it statistically significant. Result. An overall prevalence of T. vaginalis among pregnant women was 7.7% (95% with confidence interval (CI), 0.043-0.123). The highest prevalence was observed among the 35–39-year-old age group with 18.2% and among widowed women with 25%. This study revealed that the number of sexual partners (AOR: 3.215, 95% CI: 1.062-9.731) was a significant associated factor of T. vaginalis.Conclusion. The prevalence of T. vaginalis was considerably high among pregnant women in this study. This finding emphasizes the need for routine screening and treatment of pregnant women in the first antenatal care and enhances the need for regular health education for pregnant women at antenatal clinics to make them aware of their health, and avoidance of the risk of trichomoniasis is advised.